The association between a dietary index for the gut microbiota and frailty in older adults: emphasising the mediating role of inflammatory indicators - Yin, Huangyi; Qiu, Yue; Gan, Chaomei; Zhou, Yubo; Chen, Tingting; Liang, Min (Frontiers in Nutrition, 2025)
BackgroundThe dietary index for the gut microbiota (DI-GM) is a novel indicator of gut microbiome health, and its association with frailty remains unknown.MethodsWe recruited participants from the 2007–2020 National Health and Nutrition Examination Survey (NHANES). Restricted cubic splines (RCSs) and multifactorial logistic regression were employed to investigate the relationship between the DI-GM and frailty. A mediation analysis was conducted to evaluate the mediating role of inflammatory markers. Stratification and sensitivity analyses were performed to evaluate the consistency of this association.ResultsA total of 4,578 eligible individuals were screened, with a frailty prevalence of 35.50%. After adjusting for all of the covariates, each unit increase in the DI-GM was associated with a 6% decrease in the prevalence of frailty (OR = 0.94; 95% CI: 0.89, 0.99; p = 0.020). Furthermore, participants in the highest tertile of the DI-GM were significantly less likely to be frail than were those in the lowest tertile (OR = 0.70; 95% CI: 0.53, 0.91; p = 0.008). Mediation analysis revealed that inflammatory biomarkers significantly mediated the association between the DI-GM and frailty, with percentages of 16.47% for the neutrophil-to-lymphocyte ratio (NLR), 14.59% for the systemic inflammation response index (SIRI), and 11.13% for the systemic immune-inflammation index (SII). This negative relationship remained robust across subgroups and in the sensitivity analyses.ConclusionAn elevated DI-GM, which reflects a healthier microbiota state, was associated with a reduced prevalence of frailty. This relationship was partially mediated through inflammatory biomarkers.